Effects of Ionizing Radiation, United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) 2006 Report, Volume II - United Nations Scientific Committee on the Effects of Atomic Radiation (United Nations, 2009)
The purpose of this annex is to summarize the literature on non-targeted effects associated with exposure to ionizing radiation and, where possible, to evaluate how such effects may affect risks associated with radiation exposure, the understanding of radiation-induced carcinogenesis, and the mechanistic basis for interpreting epidemiological data on radiation effects.